Comparative analysis and predictive modeling of hematologic β-thalassemia minor in Pakistan: a cross-sectional study from 2019-2021 - Khan, Aftab Ahmad (International Journal of Pathology, 2024)
Background: Hypo chromic microcytic anemia happens to be the commonest form of anemia in Pakistan. Iron deficiency anemia (IDA) and Beta Thalassemia Trait (BTT) are its most common causes. Both are having similar clinical and laboratory findings. It is necessary to establish relevant cost-effective screening methods based on blood complete picture (CP) to predict BTT in order to reduce burden of Beta Thalassemia Major in Pakistani population. Methods: A cross sectional study was conducted from 2019 to 2021. 10,739 BTT or IDA suspected subjects were recruited. Blood CP was done for each patient to analyze different red cell parameters like total red blood cell count (TRBC), hemoglobin (Hb), mean cell volume (MCV), mean cell hemoglobin(MCH), mean cell hemoglobin concentration(MCHC) and red cell distribution width(RDW). For serum ferritin level, serum was collected after centrifugation and analyzed by using Abbott Alinity chemistry analyzer. Results: 1044 individuals had BTT and 270 were diagnosed as having IDA. Their RBC indices were analyzed using 25 formulae to differentiate between both conditions. Matos and Carvalho index and Pornprasert discriminative index appeared to be the most reliable indices with sensitivity, specificity, positive and negative predictive values, more than 98%. Conclusion: By utilizing Matos and Carvalho index and Pornprasert index, we can cost effectively screen huge population for BTT